(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Hemofiltration (HDF) seems to be the most effective technique in the field of renal function replacement by dialysis since it improves the general well-being of patients getting this medical procedure and cardiovascular wellness. It also raises the rate of recovery. It effectively manages hemoglobin by increasing erythropoietin levels, decreasing inflammation, and improving blood electrolyte composition.